Nilai-Nilai Religius Pada Dasa Darma Dan Implikasinya Terhadap Pembelajaran Pendidikan Agama Islam Di Sekolah - Somantri, Mut Mut Mutiah; Syahidin, Syahidin; Sumarna, Elan (PT. Student Rihlah Indonesia, 2023)
Religious Values ​​are a character or ethical way of thinking and behaving that characterizes each individual in relation to good and bad values, so that the characters that will appear become habits that are actualized in attitudes and behavior to always do good things continuously. Dasa Darma is an educational value in the Scout Movement. The formulation of the problem in this study is What are the Religious Values ​​in the Scout Movement from the formulation of the problem, the objectives to be achieved in this research are; To understand what religious values ​​are in the Scout Movement. The research method used is a qualitative research method and is a library research, namely by conducting research on written sources that are relevant to the research topic. Based on the results of the study, it can be concluded that religious values ​​in the Scout Movement can foster a spirit of mutual respect which aims to form good people who have good morals in accordance with the call of Rasulullah SAW and the goals of Indonesian education.